Metabolome and transcriptome analysis of terpene synthase genes and their putative role in floral aroma production in Litchi chinensis. Issue 6 (1st November 2022) - Abbas, Farhat; Guo, Shaoying; Zhou, Yiwei; Wu, Jing; Amanullah, Sikandar; Wang, Hui‐Cong; Shen, Jiyuan
Abstract: Volatile organic compounds (VOCs) are essential traits of flowers since they attract pollinators, aid in seed distribution, protect the plant from internal and external stimuli, and are involved in plant–plant and plant–environment interactions. Apart from their role in plants, VOCs are used in pharmaceuticals, fragrances, cosmetics, and flavorings. Litchi ( Litchi chinensis Sonn.) is a popular fruit due to its enticing red appearance, exotic taste, and high nutritional qualities. Litchi flowers bloom as inflorescences primarily on the shoot terminals. There are three distinct flower types, two male and one female, all of which are produced on the same panicle and rely on insect pollination. Herein, we used a comprehensive metabolomic approach to examine the volatile profile of litchi fruit (green pericarp, yellow pericarp, and red pericarp) as well as male and female flowers (bud stage, half open and full bloom). From a quantitative examination of the volatiles in L . chinensis, a total of 19, 22, and 21 VOCs were discovered from female flowers, male flowers, and fruits, with the majority of them belonging to sesquiterpenes. Multivariate analysis revealed that the volatile profiles of fruits differ from those of male and female flowers. Three VOCs were unique to male flowers and ten to the fruit, while eight VOCs were shared by both male and female flowers and eleven by both male and female flowers and the fruit. Furthermore, for the first time, we identified and comprehensively studied the TERPENE SYNTHASE genes ( TPS ) using the litchi genome and transcriptome database, which revealed 38 TPS genes unevenly distributed across the 15 chromosomes. A phylogenetic study showed that LcTPS were grouped into TPS‐b, TPS‐c, TPS‐e, TPS‐f, and TPS‐g subfamilies, with TPS‐b having the most genes. The conserved motifs (RRX8 W, NSE/DTE, and DDXX D) were studied in LcTPSs, and significant variation between subfamilies was discovered. Furthermore, after integrating the metabolome and transcriptome datasets, several VOCs were shown to be development‐specific and highly linked with distinct LcTPS genes, making them promising biomarkers. Interestingly, LcTPS17/20/23/24/31 were associated with monoterpene edges, while the rest were connected to sesquiterpene edges, indicating their probable participation in the aroma biosynthesis mechanism of certain compounds.